Recyclization in the Series of Spiro[indole-3,5′-pyrimido[4,5-b]quinoline]-2,2′,4′-triones Prepared by a Three-Component Reaction of Isatins with (Thio)barbituric Acids and Electron-Rich Anilines - Iaroshenko, Viktor O.; Dudkin, Sergii; Sosnovskikh, Vyacheslav Ya.; Villinger, Alexander; Langer, Peter (Synthesis, 2013)
A ring–ring transformation in the series of spiro[indole-3,5′-pyrimido[4,5-b]quinoline]-2,2′,4′-trione derivatives prepared by a three-component reaction of (thio)barbituric acids, electron-rich aromatic amines, and isatins was observed.
Keywords: multicomponent reaction; barbituric acids; aromatic amines; isatins; spiro[indole-3,5′-pyrimido[4,5-b]quinoline]-2,2′,4′-triones; recyclization